Uushenkisyys - Mahlamäki, Tiina; Opas, Minna (Tietolipas, 2022)
Contrary to the secularism thesis of the 20th century, religion did not disappear from the Western experience. Rather, religiosity took on new forms, which emphasized individuality, experientiality, and corporeality, and highlighted lifestyle consumption. These new spiritualities came to be understood as the opposite of religiosity: people identified themselves as being not religious, but spiritual. The book examines new spiritualities as a concept, a phenomenon, and a subject of research. It introduces the history of the concept and the different past approaches in the research field, and discusses the diversity of the phenomenon of new spiritualities, especially in 21st century Finland, through various case studies. The book shows the multiple ways in which new spiritualities intertwine with different sectors of the society and blur spirituality's boundary with religion, health care, art, and popular culture, for example. The book is the first book-length presentation in Finnish of the field of new spiritualities.